Complete Genome Sequence of Lily Symptomless Virus, Isolated from Alstroemeria Plants in Ecuador - Flores, Francisco (Microbiol Resour Announc, 2019)
In this work, we present the complete genome sequence of Lily symptomless virus isolated from Alstroemeria plants. The genome is 8,391-bp long, arranged into six open reading frames (ORFs), with a 5′-untranslated region (5′-UTR) of 55 nucleotides (nt) and a 3′-UTR of 48 nt.